Pendampingan Manajemen Budidaya Kambing Biri-Biri Sebagai Upaya Ketahanan Pangan Desa Bakaran Batu, Kecamatan Batang Kuis, Kabupaten Deli Serdang - Muhammad Amran; Fuad Hasan; Ade Trisna; Rico Ismail; Asmau Husna; Haryadi haryadi; Anwar Anwar (LPPI UMN AL WASHLIYAH, 2025)
This community service activity aims to increase the capacity of farmers in implementing optimal management of biri-biri goat farming as a strategy to strengthen local food security in Bakaran Batu Village, Batang Kuis District, Deli Serdang Regency. Problems faced by partner communities include low technical knowledge of cultivation, not optimal feed systems, and minimal efforts to prevent livestock diseases. Assistance is carried out through a participatory approach involving technical training, field demonstrations, and regular evaluations of aspects of cage management, feed, and animal health. The results showed significant improvements in farm management practices. In the aspect of cage management, farmers began to apply routine sanitation, stage-floored cage design, and good ventilation. In feed management, farmers were able to utilize local agricultural waste to make fermented feed, thereby reducing production costs and improving feeding efficiency. In terms of animal health, farmers began to understand the importance of vaccination, periodic deworming, and the application of basic biosecurity to prevent infectious diseases. This activity proves that cultivation management interventions based on education and empowerment can significantly contribute to household and community food security. Thus, this mentoring model has the potential to be replicated in other rural areas with similar characteristics.